The influence of leadership, job satisfaction, and work motivation on employee loyalty at PT. XYZ - Septiana, Candra; Mochamad Siddiq, Andhika; Ismail, Gurawan Dayona; Saputro, Arie Hendra (Junal Ilmu Manajemen, 2024)
Human resource management encompasses the personnel of the organization. Leadership, job happiness, and work motivation factors the company offers to its employees are crucial aspects of human resource management. These characteristics contribute to fostering employee loyalty and are critical for the organization's success. Highly loyal employees demonstrate excitement and responsibility in carrying out their duties and consistently work towards accomplishing the company's objectives. This study aims to ascertain the impact of Leadership, Job Satisfaction, and Work Motivation on Employee Loyalty at PT. XYZ. The research methodology is quantitative with a descriptive and confirmatory orientation. The sample used in this study consists of 120 respondents. The research employs multiple linear regression analysis as the chosen analytical strategy. This approach tries to uncover each independent variable's individual and combined effects on the dependent variable. The research findings classify Employee Loyalty at PT. XYZ as "Fair" categorizes the leadership at PT. XYZ, as "Fair," labels the level of job satisfaction at PT. XYZ as "Fair" and classify the work motivation at PT. XYZ as "Fair." Leadership partially influences Employee Loyalty favorably, while job satisfaction positively impacts employee loyalty. Job satisfaction has a beneficial impact on employee loyalty. Work motivation has a partially favorable impact on employee loyalty—leadership, job satisfaction, and work motivation at PT. XYZ is rated as "Fair" regarding its impact on employee loyalty.